Factores psicosociales asociados al estrés en docentes universitarios - Calva Sanchez, Martha Margoth (2018)
Abstract:The general theme of this research is "Psychosocial factors associated with stress in university teachers", the general objective was to determine the prevalence of stress and its relationship with the psychosocial and sociodemographic factors of university teachers. The research design was descriptive, correlational and transversal, with a sample of 100 teachers. Instruments: Perceived stress scale (PSS-14), Resistance scale (BRS), Perception of loneliness (UCLA), Health questionnaire for depression and anxiety patient (inflexibility (AAQ)), Life satisfaction (LSQ) and labor (WES-10). Men present a higher level of stress, although the difference between the groups is not significant. Positive correlations and disadvantages at p = 0.05 between stress and UCLA, PHQ-4, AAQ, and in the negative correlations we have: BRS and LSQ. In the sociodemographic factors, significance was found with the variable housing type (F (4,894) =, 009, p <0.05) and sex (t (98) =, 738, p> .05). The analysis was performed using T tests, ANOVA and Pearson correlation.